2011
DOI: 10.1007/s00125-011-2084-x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic implications of glucose-lowering treatment in patients with acute myocardial infarction and diabetes: experiences from an extended follow-up of the Diabetes Mellitus Insulin–Glucose Infusion in Acute Myocardial Infarction (DIGAMI) 2 Study

Abstract: Aims/hypothesis This post hoc analysis from the Diabetes Mellitus Insulin-Glucose Infusion in Acute Myocardial Infarction (DIGAMI) 2 trial reports on extended long-term outcome in relation to glucose-lowering agents in patients with myocardial infarction and type 2 diabetes. Methods Patients were randomised as follows: group 1, insulin-based treatment; group 2, insulin during hospitalisation followed by conventional glucose control; and group 3, conventional treatment. Treatment according to the above protocol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
1
5

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(72 citation statements)
references
References 37 publications
4
62
1
5
Order By: Relevance
“…In fact, previous authors have shown that insulin use may increase the risk of mortality 33. These findings allied to the risk of hypoglycemia 34 and suggestions that insulin might promote cardiovascular disease or cancers 35, 36, 37 have raised concerns regarding the safety of insulin for type 2 diabetes. However, conflicting evidence from an extended follow‐up of the trial with the biggest between‐group difference in insulin use revealed a 15% reduction in myocardial infarction and a 13% reduction in death among people with new‐onset type 2 diabetes 38.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, previous authors have shown that insulin use may increase the risk of mortality 33. These findings allied to the risk of hypoglycemia 34 and suggestions that insulin might promote cardiovascular disease or cancers 35, 36, 37 have raised concerns regarding the safety of insulin for type 2 diabetes. However, conflicting evidence from an extended follow‐up of the trial with the biggest between‐group difference in insulin use revealed a 15% reduction in myocardial infarction and a 13% reduction in death among people with new‐onset type 2 diabetes 38.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence that metformin is cardioprotective 14,15,28 raises the possibility that any cardiovascular harm of insulin may have been mitigated by metformin. However, any benefit of metformin would have also applied to the 60% of the standard-care group who used metformin.…”
Section: Insulin Glargine Bettermentioning
confidence: 99%
“…7 In addition, one trial showed increased mortality. 10 These findings, the risk of hypoglycemia, 11 and suggestions that insulin might promote cardiovascular disease or cancers [12][13][14] have raised concerns regarding the safety of insulin for type 2 diabetes. Conversely, extended follow-up of the trial with the biggest between-group difference in insulin use until now (the United Kingdom Prospective Diabetes Study [UKPDS]) revealed a 15% reduction in myocardial infarction and a 13% reduction in death among people with new-onset type 2 diabetes.…”
mentioning
confidence: 99%
“…Transition probabilities for the CHD submodel were developed using PubMed searches to identify prospective observational studies and clinical trials [39][40][41][42][43][44][45][46][47] that described various stages of CHD in patients with T2DM. Transition probabilities and references are reported in Supplementary Tables S1 and S2.…”
Section: Model Data Sources and Transition Probabilitiesmentioning
confidence: 99%
“…We used 21 outcomes and complications from six published cohort studies and randomized trials [40][41][42][44][45][46] using the new, stand-alone, CHD submodel. No other submodels from the MMD were implemented during the internal validation.…”
Section: Validation Proceduresmentioning
confidence: 99%